The banana microbiome: stability and potential health indicators - Köberl, M.; Dita, M.; Nimusiima, J.; Tumuhairwe, J.B.; Kubiriba, J.; Staver, C.; Berg, G. (Acta Horticulturae, 2018)
Banana cultivation represents one of the world’s largest monocultures, and Musa spp. belong to the most important global food commodities. Although the plantassociated microbiome has substantial influence on plant growth and health, there is limited knowledge of the banana microbiome and its influencing factors. We studied the impact of i) biogeography, ii) agroforestry, and iii) Fusarium wilt (race 1) infestation on the banana-associated gammaproteobacterial microbiome analyzing ‘Gros Michel’ (AAA genome) grown in Nicaragua and Costa Rica. Additionally, we investigated iv) the microbiome of the East African highland bananas (EAHB, AAA genome) treated with different organic soil amendment combinations of mulch and manure, and v) the microbiome stability of Xanthomonas wilt-resistant transgenic ‘Sukari Ndizi’ (AAB genome) in Uganda. Overall, the gammaproteobacterial banana microbiome was dominated by Pseudomonadales, Enterobacteriales and Xanthomonadales. An extraordinary high diversity of gammaproteobacterial microbiota was observed within the endophytic microenvironments, endorhiza and pseudostem. Enterobacteria were identified as a highly dominant group in aerial plant parts, especially of the pseudostem and leaves. Our studies show that the gammaproteobacterial banana microbiome is influenced by biogeography and banana cultivar. Work also corroborates findings that agroforestry leads to increased plant health via shifts within the microbiome. In this light, a sophisticated design of manipulating plant microbiomes can help us reduce pesticide and fertilizer use. Using gammaproteobacterial health indicators can help preventing Fusarium wilt infestation. Organic management practices lead to increased microbial soil diversity. Further studies based on more holistic population microbiology are necessary to potentially extend this behavior to the entire microbial community. Our risk assessment shows a stable microbiome for Xanthomonas wilt-resistant transgenic bananas with no consequences for non-target rhizobacteria, although additional studies should address the microbiome stability over a longer time frame.
Keywords: Agroforestry; Banana-associated microbiota; Organic soil amendments; Fusarium wilt; Xanthomonas wilt